When is indicated viscosupplementation in hip osteoarthritis? - Pogliacomi, Francesco; Schiavi, Paolo; Paraskevopoulos, Alessandro; Leigheb, Massimiliano; Pedrazzini, Alessio; Ceccarelli, Francesco; Vaienti, Enrico (Acta Biomedica Atenei Parmensis, 2018)
Background and aim The incidence of hip osteoarthritis (OA) is increasing in parallel with the aging of the population. The aim of this study is to report the efficacy of an ultrasound-guided intra-articular (IA) hip injection of a single dose of high-weight hyaluronic acid (HA) (2500 kDa) at a follow-up of 12 months. Materials and Methods 226 patients older than 40 years of age affected by painful hip OA (Kellgren–Lawrence stage 1-2-3) were treated from January 2012 to December 2015 with viscosupplementation. Patients were clinically evaluated before injection (T0) and after 3 months (T3), 6 months (T6) and 1 year (T12) through the WOMAC scale and Harris Hip Score (HHS). Results During the follow-up period no patients underwent to hip surgery or need adjunctive IA injection of HA. No adverse effects were registered. An improvement in WOMAC and HHS was observed in all patients after treatment. Results showed that patients with grade 2 of osteoarthritis had the higher delta of change in the scores. Discussion Ultrasound-guided with high weight IA HA injection could be a possibility of treatment in the symptomatic osteoarthritic hip. Subjects with a moderate grade of osteoarthritis (Kellgren–Lawrence stage 2) represent the group that could report the maximum benefits from viscosupplementation.